FACTORES ASOCIADOS A LA REALIZACIÓN DE TAMIZAJE DE MAMAS PREVENTIVOEN EL PERÚ: ENDES 2020-2024 - Benavides Luyo, Claudia Elizabeth (2025)
Introduction. Mammographic screening reduces breast cancer mortality through early detection. Objective. To analyze factors associated with preventive breast cancer screening in Peruvian women between 2020 and 2024. Methods. This was a retrospective, cross-sectional, and analytical study based on secondary data from the Demographic and Family Health Survey (ENDES) conducted between 2020 and 2024. The study population included 35 065 Peruvian women aged 35 years or older, excluding those who reported a foreign language. The outcome variable was timely breast cancer screening, defined as undergoing at least one mammogram within the last twelve months. Explanatory variables included individual-level factors (age, mother tongue, educational level, employment status, marital status, perception of cancer prevention, and health insurance coverage) and household-level factors (region, urban/rural residence, and wealth index). Poisson regression with robust variance was employed, accounting for complex survey design. Adjusted prevalence ratios (PR) with 95% confidence intervals (CI) were estimated. Statistical significance was set at p<0.05. Results. The annual prevalence of breast cancer screening was 5.8%. Higher screening rates were observed among women with secondary (PR:1.46; 95%CI: 1.09–1.97) and tertiary education (PR:2.03; 95%CI: 1.48–2.80), residents of Metropolitan Lima (PR:1.37; 95%CI: 1.13–1.65), Spanish-speaking women (PR:1.49; 95%CI: 1.13– 1.97), and those in middle (PR:1.60), high (PR:1.92), and highest (PR:3.05) wealth quintiles. A significant decrease was observed in 2021 (PR:0.66; p=0.008) compared to 2020. Conclusion. Significant educational, territorial, economic, and linguistic disparities persist in breast cancer screening uptake. Equity-focused, culturally sensitive, and territorially adapted public health strategies are urgently needed to increase coverage.